Influence of content, influencer, and product innovation on scarlett’s brand awareness through event marketing - Theresa, Erica; Rosnani, Titik; Afifah, Nur; Purmono, Bintoro Bagus; Setiawan, Harry (Junal Ilmu Manajemen, 2024)
Scarlett faces the challenge of reconciling its top rank in body lotion sales with a secondary position in overall product sales. This problem underscores the crucial need for Scarlett to apply effective marketing strategies to enhance public awareness and promote its diverse product range amid escalating competition in the market. This study aims to analyze the variables influencing brand awareness of Scarlett in Indonesia's highly competitive beauty industry. This research introduces a novel paradigm by incorporating event marketing as a variable mediating content marketing, influencer marketing, and product innovation for Scarlett. The method used in this research is Structural Equation Modeling (SEM) with the AMOS statistical tool. Data is collected through a questionnaire, with 228 respondents from Scarlett's audience. Findings demonstrate the significant influence of content marketing, influencer marketing, product innovation, and event marketing on Scarlett's brand awareness. The research also shows that event marketing can effectively serve as a mediating variable. The study's implication is to guide businesses in formulating effective marketing strategies and enhancing market positions in the dynamic digital landscape, emphasizing that brand awareness can be improved by strategically integrating event marketing with other promotional efforts, thereby contributing to a more comprehensive marketing approach.